CENTRAL ASIA AS A REGIONAL SECURITY COMPLEX1 - KLIMENKO, Ekaterina (CENTRAL ASIA AND THE CAUCASUS, 2011)
According to the Failed States Index developed by the Foreign Policy magazine, for the last five years three of the CA states, Kyrgyzstan, Tajikistan, and Uzbekistan, have been among the 60 weakest states in the world. Turkmenistan “left” this group only in 2011. Kazakhstan is the only CA state, which has been considered to be a relatively sustainable state.2 Despite these alarming statistics, the region gave the impression of relative stability. There have not been any major conflicts in CA since the Tajik civil war. However, the tragic events in the South of Kyrgyzstan of June 2010 have revealed the vulnerability of the region to various security threats. For two decades of independent existence, CA has attracted significant academic attention. Nowadays, one can distinguish several directions in the literature devoted to the analysis of CA and its particular countries. Some studies focus on the interests of great or regional powers in the region. Many scholars explore the political systems of CA countries by studying the undemocratic nature of CA regimes, while others focus on transnational threats to regional stability, such as the influence of Islamic terrorism, religious extremism, and organized crime. However, despite the wide variety of security studies on CA, until now, one can discern a lack of inclusive analysis focusing on a combination of different aspects of the regional security. The present article argues that the current security architecture in CA can be better explained by considering all levels of CA insecurity. In this regard, the combination of Barry Buzan’s Regional Security Complex theory and Karl W. Deutsch’s concept of security community proves to be a valuable tool for analyzing the regional security.